2020
DOI: 10.1080/24735132.2020.1729000
|View full text |Cite
|
Sign up to set email alerts
|

Effective wayfinding adaptation in an older National Health Service hospital in the United Kingdom: insights from mobile eye-tracking

Abstract: This case study presents a multi-phase evaluation of wayfinding difficulties in an older hospital in the UK. The first three phases made use of conventional methods for exploring wayfinding difficulties. These included a questionnaire survey for patients, a wayfinding task followed by interviews, and a questionnaire survey for stakeholders. These exercises indicated that there was a problem with wayfinding which was primarily addressed by patients and visitors asking members of staff for directions. However, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 5 publications
(6 reference statements)
0
9
0
Order By: Relevance
“…There are also some implications in using navigational color coding; it is recommended that in order to avoid visitors' confusion, only one or two destinations should be used in healthcare centers' colored lined aids on walls and floors (Rodrigues et al, 2019). Although colored lines are easy to use by most people, a study demonstrated that some people did not notice them or needed an explanation on how to use them (Ford et al, 2020). People who rely on colored lines in their wayfinding have better performance metrics (Vilar et al, 2014); however, using directional arrows beside the colored lines may help diminish possible misunderstandings (Short et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…There are also some implications in using navigational color coding; it is recommended that in order to avoid visitors' confusion, only one or two destinations should be used in healthcare centers' colored lined aids on walls and floors (Rodrigues et al, 2019). Although colored lines are easy to use by most people, a study demonstrated that some people did not notice them or needed an explanation on how to use them (Ford et al, 2020). People who rely on colored lines in their wayfinding have better performance metrics (Vilar et al, 2014); however, using directional arrows beside the colored lines may help diminish possible misunderstandings (Short et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the lowest average time registered was in task (2), registering 234.8 m and a stdv. value of 29.2 and a maximum of 480.1 m in task (11) with a stdv. of 61.87.…”
Section: First Vre Descriptive Statisticsmentioning
confidence: 99%
“…There are primarily three types of way-showing items, namely: directional devices that indicate the direction to a certain space or function, orientational devices that help the users to estimate their relative location within the environment, and defining devices that define spaces or locations [9]. Previous research has discussed the effects of various environmental elements on users' wayfinding, such as visual clutter [10,11], color [12], text [13], and verbal direction [14]. However, little research has focused on manipulating environments' wayfinding systems to achieve a better distribution of way-showing devices [15].…”
Section: Introductionmentioning
confidence: 99%
“…In a recent study, Ford et al (2020) investigate the effective wayfinding adaptation in an older National Health Service hospital in the United Kingdom by the eye-tracking method. In this study, they conducted multiphase evaluations which include survey, questionnaire, and interviews in three first phases to investigate wayfinding problems and in the fourth phase employed mobile eye-tracking combining with a wayfinding task and interview to observe visitors' navigational task to find where they looked and what kind of environmental attributes attracted their attention and for how long.…”
mentioning
confidence: 99%
“…In this study, they conducted multiphase evaluations which include survey, questionnaire, and interviews in three first phases to investigate wayfinding problems and in the fourth phase employed mobile eye-tracking combining with a wayfinding task and interview to observe visitors' navigational task to find where they looked and what kind of environmental attributes attracted their attention and for how long. In the final phase, they used an eye-tracking exercise to evaluate the recommendation were applied (Ford et al, 2020). Spiers and Maguire (2008) presented eye-tracking evidence on taxi drivers' pattern of visual attention in a Virtual Reality (VR) driving simulation of London.…”
mentioning
confidence: 99%